Perilaku dan Kekuatan Lentur Balok -T Menerus Beton Bertulang. - Perpustakaan UGM, i-lib ([Yogyakarta] : Fakultas Kehutanan UGM, 1999)
ABSTRAKS Three reinforced concrete continuous T-Beams have been examined to study the flexural strength and their behavior. Two of them are made of high strength concrete with different coarse aggregate as their main material. Firstly, the BFA beam (fc' = 68.5 MPa) contains natural coarse aggregate and the second BAKTN beam (fc' = 60.5 MPa) contains nickel slag coarse aggregate. Another beam is made of normal concrete namely, the BN beam (fc' = 29.5 MPa) as the reference. The investigation showes that the behavior of the flexural strength depends on concrete compressive strength, the higher the strength of concrete the higher the flexural strength will be. Comparisons between the flexural strength at inner support area and at load point area, yield to conclusion that the inner support area is the weakest point of the continuous T beam. In crack pattern point of view, the behavior of normal concrete is slightly different from the high strength concrete, especially after the cracking moves from the flange toward the web area. The BN beam have longitudinal cracks where such a case is not found at the high strength concrete.